Real time power quality event detection using continuous wavelet transform - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
A real time power quality event detection and logging system using continuous wavelet transform is presented in this paper. A virtual instrument concept is adopted to implement the continuous wavelet transform in real time. The measurement hardware consists of data acquisition module with USB interface and the wavelet event detection algorithm was developed using MATLAB with graphical user interface to display the wavelet coefficients in real time and the recorded waveform. The proposed algorithm is also capable to perform voltage sag and voltage transient classification for event count upon event detection. A test bench setup with voltage sag generator is used to test the performance of the proposed algorithm. With the right setting and calibration, the proposed algorithm shows superior performance with no miss detection on the test bench. This paper shows continuous wavelet transform performs in real time is made possible and it is a promising signal processing algorithm for power quality event detection application. 2011 IEEE.